Muscle hypertrophy as the presenting sign in a patient with a complete FHL1 deletion. Issue 2 (8th January 2016) - Willis, T.A.; Wood, C.L.; Hudson, J.; Polvikoski, T.; Barresi, R.; Lochmüller, H.; Bushby, K.; Straub, V.
Abstract : Four and a half LIM protein 1 (FHL1/SLIM1) has recently been identified as the causative gene mutated in four distinct diseases affecting skeletal muscle that have overlapping features, including reducing body myopathy, X‐linked myopathy, X‐linked dominant scapuloperoneal myopathy and Emery–Dreifuss muscular dystrophy. FHL1 localises to the sarcomere and the sarcolemma and is believed to participate in muscle growth and differentiation as well as in sarcomere assembly. We describe in this case report a boy with a deletion of the entire FHL1 gene who is now 15 years of age and presented with muscle hypertrophy, reduced subcutaneous fat, rigid spine and short stature. This case is the first, to our knowledge, with a complete loss of the FHL1 protein and MAP7D3 in combination. It supports the theory that dominant negative effects (accumulation of cytotoxic‐mutated FHL1 protein) worsen the pathogenesis. It extends the phenotype of FHL1 ‐related myopathies and should prompt future testing in undiagnosed patients who present with unexplained muscle hypertrophy, contractures and rigid spine, particularly if male.